Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s00296-012-2612-0
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in 11–13-year-old boys: relative importance of the weight status and body composition factors

Abstract: This study was aimed to investigate the influence of being overweight on bone mineral status in 11-13-year-old boys, who were divided into overweight (OW; n = 110) and normal weight (NW; n = 154) groups. Bone mineral density (BMD) at the whole body (WB), lumbar spine (LS) and femoral neck (FN), bone mineral content (BMC) at the WB, and body composition were assessed. Calculation of the bone mineral apparent density (BMAD) was completed for the WB, LS and FN. The BMC/height ratio was also computed. OW boys disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 42 publications
2
23
0
1
Order By: Relevance
“…These results are consistent with some studies (8,9). A previous study reported that overweight prepubertal boys had better DEXA bone parameters than that of boys with normal nutritional status (24). In our study body fat percentage did not correlate significantly to QUS in boys but did in 10-12 years old girls: a positive correlation was found between fat percentage and BUA, despite the fact that the fat% did not significantly differ between the genders in this sample.…”
Section: Anthropometry and Qussupporting
confidence: 93%
“…These results are consistent with some studies (8,9). A previous study reported that overweight prepubertal boys had better DEXA bone parameters than that of boys with normal nutritional status (24). In our study body fat percentage did not correlate significantly to QUS in boys but did in 10-12 years old girls: a positive correlation was found between fat percentage and BUA, despite the fact that the fat% did not significantly differ between the genders in this sample.…”
Section: Anthropometry and Qussupporting
confidence: 93%
“…Only the serum testosterone levels were significantly lower and the leptin levels significantly higher in the OWB compared to the NWB group. Our results showed that all bone mineral characteristics of the OWB group, except TB BMAD, were significantly higher than those of the NWB group, similar to findings published before [1,7]. …”
Section: Discussionsupporting
confidence: 81%
“…Body mass is one of the strongest predictors of BMD [2,3]. Body fat mass (FM) and fat-free mass (FFM) are both positively correlated with BMD before puberty [4,5,6] as well as during pubertal development [7,8] and in adolescence [5,9]. However, in obese children an opposite picture has been seen, namely obese children have lower BMD when adjusting for their body size [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Vigorous weight-bearing physical activity (VPA) seems to be the most effective intensity for bone growth [22,23], even though some associations have been found among bone mineral parameters and total, light or moderate PA as well, whereas the negative influence of sedentary time has been observed [24,25].…”
Section: Introductionmentioning
confidence: 99%